The Effect of Application PGR Cytokinin Against Entres Compatibility In Grafting Technique of Garcinia atroviridis plant (Garcinia atroviridis Griff ex T. Anders). - Aminah Sari Hasanah Hasibuan; Eva Sartini Bayu; Hot Setiado (Jurnal Agroekoteknologi, 2018)
The aim of the research was to determine the effect of cytokinin on the scion compatibility on the grafting union of Garcinia atroviridis. The research was conducted in Gelugur Jaya Nursery, Dusun II Bahorok, Langkat District from February 2017 to July 2017. The randomize block design (RBD) was used with 2 factors; the first factor was the rootstock type i.e; hermaphrodite rootstock and female rootstock; the second factor was the cytokinin (0 ppm, 2 ppm, 4 ppm). The result showed that the cytokinin significantly affected the number of leaves. The cytokinin with 4 ppm showed the highest number of leaves. The rootstock was not affected the whole parameters.